Correlation Study on Type and Concentration of Antimicrobial Materials on the Quality of Starch-Based Edible Film: Correlation study - Pangestika, Iga; Ulyarti, Ulyarti; Wulansari, Dian (PUI BiGME Universitas Jambi, 2022)
The purpose of this study was to determine the correlation between antimicrobial materials and several parameters of edible film quality, obtain edible film quality parameters that are likely to be affected by the use of antimicrobial materials, and determine the types of antimicrobial materials that can be used in making of starch-based edible film and their effect on the characteristics of edible film. The data used in this study were secondary data obtained from searching scientific publications. The data that were analyzed for correlation were the data on the type and concentration of antimicrobial materials and the parameters of edible films, namely wvtr, thickness, solubility, elongation, tensile strength, and moisture content. Pearson's correlation was applied in the statistical analysis using SPSS 25 statistical software application. The research showed that there was a moderate correlation between the type of antimicrobial substance and water vapor transmission rate (WVTR) and thickness of edible film. There was also a moderate correlation between the concentration of antimicrobial substance and the solubility of edible film. No correlation (level of correlation was either low or very low) was found between both the type and the concentration of antimicrobial substances and the elongation, tensile strength, and moisture content. Water vapor transmission rate, thickness, and solubility are parameters of edible film quality that are likely to be affected by the use of antimicrobial materials. White turmeric filtrate with a concentration of 0.8% is better type and concentration of antimicrobial material for use in making cassava starch-based edible films compared to other antimicrobial materials because it can affect the increase in thickness value, as well as decrease in the value of water vapor transmission rate (wvtr) and tensile strength.